Self-Efficacy, Perceived Barriers to Care, and Health-Promoting Behaviors Among Franco-Americans Across Cardiovascular Risk Factors: A Cross-Sectional Study. Issue 5 (June 2021) - Mszar, Reed; Buscher, Sara; McCann, Dervilla; Taylor, Heidi L.
Purpose: To assess the prevalence of perceived barriers to accessing health care services, self-efficacy, and health-promoting behaviors among Franco-Americans as a higher-risk group for familial hypercholesterolemia (FH), stratified by cardiovascular risk factors. Design: Cross-sectional survey based on components of the Health Belief Model Setting: Administered in-person at a Franco-American cultural center and online through mailing lists and social media platforms in the Northeastern United States Sample: Franco-Americans and French Canadians (n = 170) Measures: Demographic and clinical characteristics (i.e. high cholesterol, prior heart attack or stroke, family history of atherosclerotic cardiovascular disease (ASCVD), diagnosis of FH), perceived barriers to accessing health care services, self-efficacy, and health-promoting behaviors (i.e. taking lipid-lowering medications, seeing a cardiovascular specialist). Results: In a cohort of Franco-Americans, 42 (25%) had both high cholesterol and family history of ASCVD. Among Franco-Americans with both cardiovascular risk factors, 22% had low self-efficacy and only 16% had discussed FH with their physician. Individuals with both risk factors were significantly more likely to report a concern over a future diagnosis as a barrier to accessing health care services when compared with those with neither risk factor (36% vs. 15%, p = 0.014). Overall, other prominent barriers to care included knowledge of when to seek help (27%) and a distrust in medicine (26%). Conclusion: Franco-Americans report significant barriers to accessing health care services. Our findings strengthen the case for developing focused public health strategies to raise awareness for FH, particularly among high-risk subpopulations with unmet cardiovascular needs.